Use of prefabricated panels as a lean construction strategy - Saraiva, Oscar Vinícius Santana; Holanda, Samuell Aquino; Freire, Pedro Mandú (Brazilian Journal of Production Engineering, 2025)
The increasing competitiveness in the construction industry has driven companies to adopt new construction techniques and management strategies. Lean Construction, based on Koskela’s (1992) theoretical framework, aims to reduce waste, improve production flows, and deliver greater value. This study analyzes the alignment of the Olé Casas system, which employs prefabricated panels, with the eleven principles of Lean Construction. Data were collected through on-site visits and document analysis, and compared against theoretical frameworks. Results show that the Olé Casas system aligns well with Lean Construction principles, particularly regarding standardization, production cycle reduction, and variability control.
Keywords: Lean Construction; Prefabricated panels; Lean Philosophy